Cerebellar Transcranial Direct Current Stimulation Modulates Corticospinal Excitability During Motor Training - Summers, Rebekah L. S.; Chen, Mo; Hatch, Andrea; Kimberley, Teresa J. (Frontiers in Human Neuroscience, 2018)
Background: Cerebellar activity can be modulated using cerebellar transcranial direct current stimulation (ctDCS) and, when applied concurrently with task training, has been shown to facilitate cognitive and motor performance. However, how ctDCS facilitates motor performance is not fully understood. Objective/Hypothesis: To assess the electrophysiological and motor performance effects of ctDCS applied during motor training. Methods: 14 healthy adults (age 28.8±10.5 years) were randomly assigned to complete one session of finger tracking training with either simultaneous bilateral anodal or sham ctDCS. Training was completed in two 15 min epochs with a 5-min break (total 30min stimulation, 2mA). Tracking accuracy and corticospinal and intracortical excitability were measured immediately before and after the training period. Motor cortical excitability measures included resting motor threshold (RMT), motor evoked potential (MEP) amplitude, cortical silent period (CSP), and short interval intracortical inhibition (SICI). Results: MEP amplitude change scores were significantly different between groups (p = 0.014). MEP amplitude was increased in the sham group (p < 0.001), indicating increased corticospinal excitability from baseline while the anodal group displayed a decrease in MEP amplitude (p = 0.003). There were no between group differences for RMT (p = 0.948), CSP (p = 0.275), SICI (p = 0.354) or task accuracy (p =0.482). Conclusions: ctDCS applied during task training is capable of modulating or interfering with practice-related changes in corticospinal excitability without disrupting performance improvement.